MENEMUKAN INKLUSIFITAS INTERAKSI SOSIAL ANTAR UMAT BERAGAMA PADA MASYARAKAT MULTIKULTURAL - Sugiyar - (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
Multicultural and diversity of society is a reality at once the inevitability. This shows the condition of the multicultural society, such as the existence of a diversity of cultural, ethnic, language, race, and religion. Diversity can bring up problems or internal and external conflicts on the one hand, and at once became a chance to build a multicultural society life character humanist, tolerant, democratic, and harmonious. The community internally bound by norms, values, and traditions to create a secure life, peace, tenets, and harmonious. Harmonious society always seeks the democratic spirit and upholding human rights. Various attempts made to find the ideal format to create harmony in the social interaction between people of religion, so that the existence of religion and religious life in society can be well maintained.